The Effect of Weld Current and Weld Time on the Push Test, Nugget and Penetration Depth of Steel Plate SPFC590 with Weld T-Nut M10 - Ardhi Alfarizzi Tanjung; Budiarto Budiarto; Surjo Abadi (Politeknik Negeri Lhokseumawe, 2023)
This study explains the effect of the parameters of current strength and welding time. The welding process uses SPFC590 t1.2 steel plate material and Weld T-Nut M10 with a 50 kVA Dagensha brand spot welding process. The purpose of this research is to analyze the push test, nugget, and depth of penetration against engineering standards from PT HMC (Hyundai Motor Company). Using the factorial experimental design method to convey test layout formulations, understand the best conditions for setting machine parameters, and knowing the performance effect of parameter settings such as push tests, nuggets, and depth of penetration spot welding. The results of the push test between the SPFC590 t1.2 steel plate and Weld T-Nut M10 are the largest 17.7 kN and the smallest 15.4 kN. the test results have passed the results of the 6.5 kN engineering standard. Test results on nuggets the longer the melting occurs the wider the growth of the melt, and after the part is at room temperature the melting zone will become a nugget, for the average nugget test result is 5.6 mm and has passed the standard engineering results. Whereas in the penetration test the longer the welding time the deeper the penetration depth. The results showed that the parameters of current strength and welding time can affect the results of the size of the nugget and the depth of penetration of spot welding, but can reduce the strength of the push test. besides that the less the remaining plate that is not affected by penetration the smaller the strength of the push test, and the less depth of penetration. The smaller the strength of the push test and the higher the current strength and welding time, the larger the nugget size obtained.